CRISPR/Cas9-Mediated Targeting of Susceptibility Factor eIF4E-Enhanced Resistance Against Potato Virus Y - Noureen, Azka; Khan, Muhammad Zuhaib; Amin, Imran; Zainab, Tayyaba; Mansoor, Shahid (Frontiers in Genetics, 2022)
Potato (Solanum tuberosum L) is an important staple food around the world, and potato virus Y (PVY) is a major constraint to potato production. The VPg of PVY interacts with the initiation factor eIF4E, that works as a susceptibility factor during infection. The interaction between eIF4E protein and VPg has been disrupted by CRISPR/Cas9. A homozygous conserved region of eIF4E of potato variety Kruda was mutated by CRISPR/Cas9. Tracking of insertion, deletion and conversion events were confirmed by Sanger sequencing with ~15% editing efficiency. Truncated and mutated eIF4E proteins unable to interact with VPg and virus was note able to exploit the host machinery for replication and systemic spreading as judged by the symptoms. Mutated eIF4E lines showed enhanced resistance to PVYO strain. DAS-ELISA and RT-PCR validated the results of phenotype produced in transgenic plants. This is the first study to use CRISPR/Cas9 in cultivated potatoes to generate immunity to PVY. CRISPR/Cas9 resistance in tetraploid lines allows the development of new resistant potato cultivars.